Smart Office System Based Internet of Things - Sirojul Hadi; Kurniawan Aji Pangestu (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
A smart office system is a complex system. The system consists of software and hardware that are interconnected with existing equipment in the office. With the Internet of Things (IoT) technology, it can facilitate the smart office system in the process of data communication through the internet network. The research was conducted at PT. Media Facilities Data Area NTB. The company is an internet service company headquartered in the Denpasar, Bali regional office. The company has a complaint about the lack of facilities to monitor and control facilities located in area offices throughout the province of West Nusa Tenggara (NTB). The complaint occurs because the service area is growing, there will be more branch offices in the area to accommodate the teams and services in each branch so that it will be increasingly difficult to monitor and control each of these offices. The method used in designing the smart office system is the research and development (R&D) method. Smart office system aims to make it easier to monitor and control equipment and assets in the office. The result of this research is that the design and implementation of the smart office system have been successfully built. The system can facilitate the HRGA (Human Resource and General Affairs) department in managing and monitoring employees, internet networks and office facilities. The system design that has been built has been successfully tested with a success rate of 100% RFID card reading, 90% control over office facilities, and 80% attendance data.